Hubungan Kreativitas dengan Hasil Belajar Pengelolaan Usaha Boga Mahasiswa Jurusan Ilmu Kesejahteraan Keluarga Fakultas Pariwisata dan Perhotelan - Murni, Ravika; Syarif, Wirnelis; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aimed to describe the relationship of creativity with the results of student learning Science Department of Family Welfare in the subject of Business Management Catering Faculty of Tourism and Hospitality UNP. This study is quantitative with a population of 96 students and 48 students were sampled. Data collection techniques for the creativity of students using a questionnaire (questionnaire). The results showed that the creativity of students in the subject of Business Management Catering categorized enough (77%), while the results of student learning categorized as good (50%).Correlation test results showed that there is a positive and significant relationship between the creativity of students learning outcomes with tcount 0.619 Significant padataraf 0.000.Keywords: Creativity, Learning Outcomes